Preparation and Characterisation of Polystyrene Grafted Sago Starch - Janarthanan, Pushpamalar (1999)
Styrene grafting onto sago starch was carried out by using eerie ammonium nitrate (CAN) as a redox initiator. The parameters affecting the grafting reaction were investigated and the optimum conditions obtained are as follows: temperature, 50°C; nitric acid concentration, 0.01 M; amount of styrene, 0.35 mol; amount of CAN, 16.8 x 10-4 mol and reaction period, 2h. Percentages of grafting and grafting efficiency under the optimum condition were 53.92% and 73.21%, respectively. Reactions in the presence of nitrogen gas resulted in higher percentages of grafting and grafting efficiency. FTIR spectra analysis of the grafted chain and polystyrene was identical indicating that styrene was successfully grafted onto sago starch. TGA thermograms, DSC curves and SEM photographs of sago starch-g poly(styrene) and the original polymers (sago starch and polystyrene) were different which suggested that styrene was grafted onto sago starch. The bio-degradability study using a-amylase showed that the rate of degradation of gelatinised sago starch was higher than that of sago starch-gpoly( styrene). The highest rate of degradation of sago starch-gpoly(styrene) was obtained at 50 ppm of a-amylase concentration. Viscosity measurements showed that the intrinsic viscosity and the average molecular weight (Mv) increased with the increase in the percentage of grafted polystyrene. The Mv of the various percentages of grafted polystyrene were in the order of 104. The results obtained from the swelling of sago starch-gpoly(styrene) in polar and non polar solvents showed that the percentage of swelling at equilibrium and the swelling rate coefficient decreased in the following order: DMSO > water > acetone > cyclohexanone = CHCh > toluene = CCl4. Diffusions of the solvents onto the polymers were found to be of a Fickian only for DMSO.